2015
DOI: 10.7717/peerj.1102
|View full text |Cite
|
Sign up to set email alerts
|

The majority are not performing home-exercises correctly two weeks after their initial instruction—an assessor-blinded study

Abstract: Introduction. Time-under-tension (TUT) reflects time under load during strength training and is a proxy of the total exercise dose during strength training. The purpose of this study was to investigate if young participants are able to reproduce TUT and exercise form after two weeks of unsupervised exercises.Material and Methods. The study was an assessor-blinded intervention study with 29 participants. After an initial instruction, all participants were instructed to perform two weeks of home-based unsupervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 34 publications
(74 reference statements)
2
54
0
2
Order By: Relevance
“…Wang et al 55 found that optimising the vastus medialis (VM) size was critical to reducing osteoarthritic progression and decreasing the need for a total knee replacement. Recent evidence of the long-term outcome of treatment for adolescents with AKP, who are supposedly compliant with a multimodal exercise programme, is fairly poor, although the same authors found that the majority of adolescents did not perform the home exercises correctly 2 weeks after their initial instruction 56. It is hypothesised that the adolescents whose symptoms fail to improve will develop PFOA 57.…”
Section: Non-operative Treatmentmentioning
confidence: 99%
“…Wang et al 55 found that optimising the vastus medialis (VM) size was critical to reducing osteoarthritic progression and decreasing the need for a total knee replacement. Recent evidence of the long-term outcome of treatment for adolescents with AKP, who are supposedly compliant with a multimodal exercise programme, is fairly poor, although the same authors found that the majority of adolescents did not perform the home exercises correctly 2 weeks after their initial instruction 56. It is hypothesised that the adolescents whose symptoms fail to improve will develop PFOA 57.…”
Section: Non-operative Treatmentmentioning
confidence: 99%
“…Treatment decisions are based on the functional knee stability measured through functional performance tests and the child's experience in their desired activities. There is substantial support in the literature that rehabilitation should be supervised [13], and performed exhaustively before a decision on further treatment is made for an ACL injured patient [39,45]. Preoperative rehabilitation is beneficial because it increases the likelihood of a successful outcome after ACL reconstruction -and is in many cases effective in restoring functional knee stability to a level that eliminates the need for a surgical ACL reconstruction [15,25,69].…”
Section: Rehabilitation Algorithmsmentioning
confidence: 99%
“…After the physiotherapist provides the patient with initial instructions on how to perform the exercise, home-based trainees need to complete the entire training program on their own. Without the supervision of a therapist or help of an exercise monitoring system, and considering that the training is a long process that lasts weeks or months, one of the biggest challenges in home-based resistance training is that subjects do not follow their exercise prescription [9,10,11]. In particular, it has been shown that patients perform the exercises either too fast or too slow, resulting in too short or too long contraction time with too few or too many repetitions [12].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that patients perform the exercises either too fast or too slow, resulting in too short or too long contraction time with too few or too many repetitions [12]. A study of 29 participants performing shoulder abduction exercises demonstrated that, at follow-up after two weeks of unsupervised home-based exercises, less than 25% of the participants followed the instructions for time-under-tension (TUT) and performed correctly the exercise [10]. The main concern for patients not receiving the prescribed exercise dosage is that decisions on further progression or cessation of a specific program are difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation